Polska w prasie ukraińskiej (na przykładzie tygodników „Ukraiński tydzień”, „Fokus”, „Korrespondent” i gazety „Kommentarii”) - Konsewic, Olga (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
The paper describes publications about Poland in the Ukrainian press. The author analyses the weekly news magazines “Ukrainskyi Tyzhden,” “Focus,” “Korrespondent” and the “Kommentarii” newspaper in 2012. Particular attention is given to the subjects of the publications. The position of the Ukrainian mass media is important in improving bilateral relations. The analysis of publications about Poland reveals the trends in information policy and the formation of Poland’s image among Ukrainians.